Protocolo de profilaxis antibiótica para pacientes dentales en riesgo de infección - Astudillo-Crespo, María Isabel (2022)
Antibiotic prophylaxis involves the use of drugs at a preoperative stage of dental care, with a specific aim of contributing to the prevention of systemic infections such as infectious endocarditis (IE) associated with transient bacteremia due to dental procedures that involve bleeding in patients at high risk of complication due to their non-cardiac or cardiac systemic condition. This potential complication inflames the inner lining of the heart valves, due to the proliferation of specific microorganisms, and although it is uncommon, it is responsible for a high rate of morbidity and mortality. In 2007, the American Heart Association (AHA) published the last current update in the literature on the recommendations and guidelines applied for the use of antibiotic prophylaxis. The aim of this review is to develop a synthesis of existing evidence followed by an honest assessment of the risks and benefits individually on the use of this protocol. A comprehensive digital search was conducted in both Spanish and English on antibiotic prophylaxis protocols in patients at risk of infection. Databases such as MEDLINE, PUBMED, and SciELO were included, in addition the AHA recommendations were taken as baseline references. It is concluded with great emphasis and support from the current literature, that the benefits of the use of antibiotic prophylaxis in a preoperative moment overcome the possible risks of bacterial resistance and anaphylaxis, so they are fully justifiable and required for immunologically compromised adult and children patients.